Neptune Orient Lines Ltd.: Sailing Through Uncharted Sea - Khoo, Beng Kiat (1999)
In the early Monday morning of April 10, 1999, sits Joseph Flemming in front of the classy window of NOL (Neptune Orient Lines Ltd.) air-conditioned penthouse. Joseph was holding a cup of freshly brewed coffee while staring far to appreciate Singapore's natural scenic view of the early sun rising. Below, contradicting to the natural view, a bunch of executives were rushing across the busy traffic just right in front of the NOL Group's landmark building, a high rise of 21 floors building. It was 8:45 am in the morning, and Joseph Flemming, a newly appointed two-month-old CEO (Chief Executive Officer) of NOL Group, was already keen to get down to his job. He likes to work as early as 7:45 am every morning and more often than not on weekends as well. Joseph Flemming, a man in his mid- 60, who believes in getting results through hard work, was commented by a former colleague in Maersk Lines, another world's top ranking shipping lines, as a workaholic, being very hands on, open to suggestions and critiques, impatient to get things done, always on the look for opportunity and way to get thing done better. The enchanting, high rise morning view was really a bonus for Joseph to start off his daily routine early.